The effect of breastfeeding counseling using card media on the knowledge and skills of breastfeeding mothers using the Quasy Experiment research approach - Anis, Jumrotul; Supariasa, I Dewa Nyoman; Fajar, Ibnu; Prasetyo, Yoyok Bekti (BKM Public Health and Community Medicine, 2023)
Purpose: This research aims to analyze the effect of breastfeeding counseling cards on the knowledge and breastfeeding skills level in mothers of babies 0-6 months. Methods: This research used a quasi-experimental design with two treatment groups. The research sample of 30 respondents was calculated with the help of G-Power Analysis 3.1 based on a 2-group t-test with an alpha error of .05, power of study 0.80, and large effect size (0.9). Results: The average age of breastfeeding mothers is 26.7 years, with the majority education level being senior high school (SMA) at 63.3% and the number of children at one level being 53.3%. Counseling with cards had a significant effect on the level of knowledge of breastfeeding mothers (p < 0.000). Counseling also significantly affects changes in skills (p < 0.000). The intensity of counseling is also a factor that influences the improvement of the mother's skills, so the more frequent contact between the mother and the counselor, the more often the mother will receive information, indirectly improving the mother's skills. Conclusion: The results of this study can be used as a reference for further research related to breastfeeding counseling and exclusive breastfeeding. The results of this research can be developed with other media, both print and electronic media, by taking advantage of advances in technology and society that continue to develop to increase the knowledge and skills of breastfeeding mothers and achieve exclusive breastfeeding.